2006
DOI: 10.1681/asn.2005060616
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Anti–TNF-α Antibodies in an Experimental Model of Anti-Neutrophil Cytoplasm Antibody–Associated Systemic Vasculitis

Abstract: The therapeutic options for anti-neutrophil cytoplasm antibody (ANCA)-associated systemic vasculitis (AASV) remain limited and hampered by adverse effects. One potential novel therapeutic avenue involves inhibition of TNF-␣, with encouraging uncontrolled data in humans with one agent (infliximab) but disappointing controlled data from another (etanercept). For investigating the potential role of TNF-␣ as a therapeutic target in AASV, the effect of an anti-rat TNF-␣ mAb (CNTO 1081) in a rat model of AASV was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 40 publications
3
66
0
Order By: Relevance
“…1,2 Animal models firmly establish the importance of anti-MPO antibody and neutrophils for the induction of vasculitis and NCGN. 3,27,28 Although monocytes also express ANCA (E and F) bone marrow stained with GR-1 for PMN and CD68 for MoMa. **P,0.01.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Animal models firmly establish the importance of anti-MPO antibody and neutrophils for the induction of vasculitis and NCGN. 3,27,28 Although monocytes also express ANCA (E and F) bone marrow stained with GR-1 for PMN and CD68 for MoMa. **P,0.01.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Animal models firmly established ANCA pathogenicity for NCGN. [5][6][7][8][9][10] Numerous in vitro experiments suggest that phagocyte NADPH oxidase (Nox) and granule proteins, including neutrophil serine proteases (NSPs), participate in ANCA-mediated endothelial damage. 2,[11][12][13] We used a murine ANCA NCGN model and recently showed that IL-1b provides an important disease mediator and that proteolytically active NSPs are essential for processing pro-IL-1b to IL1b.…”
mentioning
confidence: 99%
“…With use of these model systems, TNF␣, complement, chemokines, and integrins were identified as potential targets. [22][23][24][25][26] We optimized an MPO-ANCA mouse model and showed that the complement receptor C5a and the PI3K␥ isoform are novel targets. 27,28 We used this model to assess NCGN with the 26S proteasome inhibitor bortezomib (BTZ), compared with standard steroid/cyclophosphamide (S/CYC) treatment.…”
mentioning
confidence: 99%